Inclusion of Disadvantaged People in National Open University of Nigeria: Correctional Services Inmates’ Perspective - Akpan, Louis O.; Mayowa-Adebara, Okeoghene; Oluwatuyi, Omolara Joy (West African Journal of Open and Flexible Learning, 2023)
National Open University of Nigeria (NOUN) has taken university education to the door-step of Nigeria Correctional Service (NCS). The hitherto marginalised prison inmates have been provided with opportunity to have access to university education within the confine of correctional facilities in the country. The study explores inclusion and impact of Nigerian correctional inmates to university education in Nigeria. The study is located within the pedestal of qualitative method. In line with qualitative approach adopted, interpretive paradigm was employed to make sense of the inmates’ narrative. The researcher purposively selected twenty-one inmates for the study. Due to the sensitive nature of the study, all ethical issues were adhered to. Semi-structured interview was developed and administered on the participants. The information gathered were transcribed, coded, categorised and emerging themes analysed using narrative analysis. Findings indicated that inmates perceived university education as human development, and crime prevention and control strategies. Furthermore, the inmates stated that the acquisition of university degree has impacted their self-actualisation and offered them various opportunities for employment after jail term. Based on the findings, it was recommended among others that Federal Government should focus on supporting rehabilitation through provision of secondary and university education in order to reduce recidivism. Résumé : La National Open University of Nigeria (NOUN) a étendu l’éducation universitaire aux portes du Nigeria Correctional Service (NCS) <<Les Services Correctionnels du Nigeria>>. Les détenus, autrefois marginalisés, ont désormais la possibilité d’accéder à l’enseignement universitaire dans les établissements correctionnels du pays. L’étude explore l’inclusion et l’impact des détenus nigérians sur l’enseignement universitaire au Nigeria. L’étude s’inscrit dans le cadre de la méthode qualitative. Conformément à l’approche qualitative adoptée, un paradigme interprétatif a été utilisé pour donner du sens au récit des détenus. Le chercheur a sélectionné délibérément vingt et un détenus pour l’étude. En raison de la nature sensible de l’étude, toutes les questions éthiques ont été respectées. Un entretien semi-structuré a été élaboré et administré aux participants. Les informations recueillies ont été transcrites, codées, catégorisées et les thèmes émergents ont été analysés à l’aide de l’analyse narrative. Les résultats indiquent que les détenus considèrent l’éducation universitaire comme un développement humain, ainsi que des stratégies de prévention et de contrôle du crime. De plus, les détenus ont déclaré que l’obtention d’un diplôme universitaire a eu un impact sur leur auto-réalisation et leur a offert diverses opportunités d’emploi après leur peine. Sur la base des résultats, il a été recommandé, entre autres, que le Gouvernement Fédéral se concentre sur le soutien à la réhabilitation en fournissant une éducation secondaire et universitaire afin de réduire la récidive. Mots-clés : Inclusion, Détenus du Service Correctionnel, NOUN, Enseignement Universitaire